Protein Modification with Amphiphilic Block Copoly(2-oxazoline)s as a New Platform for Enhanced Cellular Delivery - Tong, Jing (2010)
Several homo-, random and block copolymers based on poly(2-oxazoline)s (POx) were synthesized and conjugated to horseradish peroxidase (HRP) using biodegradable and non-biodegradable linkers. These conjugates were characterized by amino group titration, polyacrylamide gel electrophoresis (PAGE), isoelectric focusing, enzymatic activity assay and conformation analysis. The conjugates contained on average from about one to two polymer chains per enzyme. From 70% to 90% of enzymatic activity was retained in most cases. Circular dichroism (CD) analysis revealed that HRP modification affected the secondary structure of the apoprotein but did not affect the tertiary structure and heme environment. Enhanced cellular uptake was found in the conjugates of two block copolymers using both MDCK cells and Caco-2 cells, but not in the conjugates of random copolymer and homopolymer. Conjugation with a block copolymer of 2-methyl-2-oxazoline and 2-butyl-2-oxazoline led to the highest cellular uptake as compared to other conjugates. Our data indicates that modification with amphiphilic POx has the potential to modulate and enhance cellular delivery of proteins.